Respiratory viruses in acute exacerbations of chronic obstructive pulmonary disease - Parvaiz A Koul; Hyder Mir; Shabir Akram; Varsha Potdar; Mandeep S Chadha (Lung India, 2017)
Objective: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) cause significant morbidity, mortality, and an inexorable decline of lung function. Data from developed countries have shown viruses to be important causes of AECOPD, but data from developing countries like India are scant. We set out to determine the contribution of viruses in the causation of hospitalized patients with AECOPD. Methods: Twin nasopharyngeal/oropharyngeal swabs collected from 233 patients admitted with an acute AECOPD and tested for respiratory viruses including respiratory syncytial virus A and B, parainfluenza were (PIV) 1, 2, 3, and 4, human metapneumovirus (hMPV) A and B, influenza A and B, enterovirus, corona NL65, OC43, and 229E viruses, adenovirus 2 and 4, rhinovirus, and bocavirus, by duplex real time reverse-transcription polymerase chain reaction (qRT-PCR) using CDC approved primers and probes. Samples positive for influenza A were subtyped for A/H1N1pdm09 and A/H3N2 whereas influenza B samples were subtyped into B/Yamagata and B/Victoria subtypes, using primers and probes recommended by CDC, USA. Results: Respiratory viruses were detected in 46 (19.7%) cases, influenza A/H3N2 and rhinoviruses being the most common viruses detected. More than one virus was isolated in four cases consisting of hMPV-B + adeno-2 + Inf-B; rhino + H3N2, PIV-1 + rhino; and PIV-1+ hMPV-B in one case each. Ancillary supportive therapeutic measures included bronchodilators, antibiotics, steroids, and ventilation (noninvasive in 42 and invasive in 4). Antiviral therapy was instituted in influenza-positive patients. Three patients with A/H3N2 infection died during hospitalization. Conclusions: We conclude that respiratory viruses are important contributors to AECOPD in India. Our data calls for prompt investigation during an exacerbation for viruses to obviate inappropriate antibiotic use and institute antiviral therapy in viral disease amenable to antiviral therapy. Appropriate preventive strategies like influenza vaccination also need to be employed routinely.